Advanced chronic liver disease in the last year of life: a mixed methods study to understand how care in a specialist liver unit could be improved. Issue 8 (29th August 2017) - Low, Joseph; Davis, Sarah; Vickerstaff, Victoria; Greenslade, Lynda; Hopkins, Katherine; Langford, Andrew; Marshall, Aileen; Thorburn, Douglas; Jones, Louise
Abstract : Objective: To identify the limitations in palliative care provision in the last year of life for people with liver cirrhosis and potential barriers to and enablers of palliative care. Design: Mixed methods, including a retrospective case note review, qualitative focus groups and individual interviews. Setting: A tertiary referral liver centre in the south of England (UK). Participants: Purposively selected case notes of 30 people with cirrhosis who attended the tertiary referral liver centre and died during an 18-month period; a purposive sample of 22 liver health professionals who participated in either focus groups or individual interviews. Primary and secondary outcomes: Data collected from case notes included hospital admissions, documented discussions of prognosis and palliative care provision. Qualitative methods explored management of people with cirrhosis, and barriers to and enablers of palliative care. Results: Participants had high rates of hospital admissions and symptom burden. Clinicians rarely discussed prognosis or future care preferences; they lacked the skills and confidence to initiate discussions. Palliative care provision occurred late because clinicians were reluctant to refer due to their perception that reduced liver function is reversible, poor understanding of the potential of a palliative approach; palliative care was perceived negatively by patients and families. Conclusions: People dying with cirrhosis have unpredictable trajectories, but share a common pathway of frequent admissions and worsening symptoms as death approaches. The use of clinical tools to identify the point of irreversible deterioration and joint working between liver services and palliative care may improve care for people with cirrhosis.